Tumour TIF1 mutations and loss of heterozygosity related to cancer-associated myositis - Pinal-Fernandez, Iago; Ferrer-Fabregas, Berta; Trallero-Araguas, Ernesto; Balada, Eva; Martínez, Maria Angeles; Milisenda, Jose César; Aparicio-Español, Gloria; Labrador-Horrillo, Moises; Garcia-Patos, Vicente; Grau-Junyent, Josep M; Selva-O'Callaghan, Albert (Rheumatology (Oxford, England), 2018)
Abstract Objectives To analyse the influence of genetic alterations and differential expression of transcription intermediary factor 1 (TIF1) genes in the pathophysiology of cancer-associated myositis (CAM). Methods Paired blood and tumour DNA samples from patients with anti-TIF1γ-positive CAM and from controls were analysed by whole-exome sequencing for the presence of somatic mutations and loss of heterozygosity (LOH) in their TIF1 genes. The genesis and maintenance of the autoimmune process were investigated immunohistochemically by studying TIF1γ expression in the different tissues involved in CAM (skin, muscle and tumour) based on the immunohistochemical H-score. Results From seven patients with anti-TIF1γ-positive CAM, we detected one somatic mutation and five cases of LOH in one or more of the four TIF1 genes compared with just one case of LOH in tumours from TIF1γ-negative myositis patients (86% vs 17%; P = 0.03). Compared with type-matched control tumours from non-myositis patients, TIF1γ staining was more intense in tumours from anti-TIF1γ-positive patients (H-score 255 vs 196; P = 0.01). Also, TIF1γ staining in muscle was slightly more intense in anti-TIF1γ-positive than in anti-TIF1γ-negative myositis (H-score 22 vs 5; P = 0.03). In contrast, intense TIF1γ staining was detected in the skin of both myositis and control patients. Conclusion Tumours from paraneoplastic anti-TIF1γ-positive patients showed an increased number of genetic alterations, such as mutations and LOH, in TIF1 genes. These genetic alterations, in the context of a high expression of TIF1γ in the tumour, muscle and skin of these patients may be key to understanding the genesis of paraneoplastic myositis.